BANYUMAS PROPER NAMES: STRUCTURE AND CULTURAL REFLECTION - Gita Anggria Resticka; Erwita Nurdiyanto; Sri Nani Hari Yanti (UIN Raden Mas Said Surakarta, 2021)
Proper name is a linguistic symbol that reflects people’s perspectives and thoughts over something. This study aims to reveal current naming convention in Banyumas from linguistic perspective and to describe naming classification which covers list of proper names, their sociocultural background, the meanings, and the functions. This study used descriptive-qualitative method with snowball technique for the sampling. Banyumas proper names are dominated by the use of monomorphemic form. The languages used to give proper names come from local language, Bahasa Indonesia, as well as foreign languages.The naming structure covers first name, functioning as gender and birth order markers; middle name, containing ethnical or foreign element; and last name, containing family name. Naming reference mostly uses adjectives, famous figures’ names, nature elements, flower names, puppet characters’ names, and/or numbers and symbols. Prefix su- also characterizes some proper names in Banyumas. Cultural reflection from Banyumas proper names is that the proper names chosen by the name givers, mostly parents, resemble their hope and prayer for their children. Proper name as a part of culture and folklore becomes ethnical identity for the people themselves.